2022
DOI: 10.1101/2022.05.03.490382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping mechanical stress in curved epithelia of designed size and shape

Abstract: The function of organs such as lungs, kidneys and mammary glands relies on the three-dimensional geometry of their epithelium. To adopt shapes such as spheres, tubes and ellipsoids, epithelia generate mechanical stresses that are generally unknown. Here we engineered curved epithelial monolayers of controlled size and shape and mapped their state of stress. We designed pressurized epithelia with circular, rectangular and ellipsoidal footprints. We developed a computational method to map the stress tensor in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 70 publications
2
12
1
Order By: Relevance
“…This mechanism identified in a synthetic system was later established in vivo during drosophila gastrulation [63]. More recent studies also took advantage of closed-dome structures to map stresses on domes of different shapes [61] and built domes from human stem cells [7], with an elongated footprint to mimic the neural tube geometry. Here, stem cells seeded on rectangular patterns were covered with Matrigel and subsequently self-organized into a tissue bilayer.…”
Section: Domesmentioning
confidence: 96%
See 1 more Smart Citation
“…This mechanism identified in a synthetic system was later established in vivo during drosophila gastrulation [63]. More recent studies also took advantage of closed-dome structures to map stresses on domes of different shapes [61] and built domes from human stem cells [7], with an elongated footprint to mimic the neural tube geometry. Here, stem cells seeded on rectangular patterns were covered with Matrigel and subsequently self-organized into a tissue bilayer.…”
Section: Domesmentioning
confidence: 96%
“…Domes are curved, lumenized epithelial structures attached to a substrate [60,61] (Figure 2C-C'). They can be used to model lumen-filled in vivo organs like the healthy blastocyst or the otic vesicle, as well as diseased organs like the polycystic kidney, with more control than free-floating 3D spheres that we discussed above.…”
Section: Domesmentioning
confidence: 99%
“…Folding is a distinctive feature of embryonic transformation allowing to acquire a three-dimensional structure driven either by differential growth [3] or by active contractility [4]. In both case, folding emerges as a mechanoadaptation process with the formation of invaginations/evaginations as the cellular tissue behaves as an elastic membrane [5,6]. In many biological system models, folding may lead to the inversion of the cellular assembly, in order to fulfil a biological function, such as the assembly of the adult exoskeleton in the Drosophila disc [7] and the telencefalic develoment in mammals and teleosts [8].…”
Section: Introductionmentioning
confidence: 99%
“…Not just 2D shape, epithelial monolayers are also able to respond to curvature by regulating cell migration, orientation, cell/nucleus size, and shape (Marín-Llauradó et al, 2022, Schamberger et al, 2022 (see fig 2.3 C). For example, an epithelial monolayer on hemispheres of elastomers acts as a fluid with increasing curvature (Tang et al, 2022).…”
Section: Geometric Controlmentioning
confidence: 99%
“…Second, epithelial domes, where MDCK cells pump ions to form fluid-filled blisters, have been used (Lever, 1979). Recently, my colleagues, Ernest Latorre and Ariadna Marin-Llaurado, have enhanced control over the curvature, shape, and size of the domes (Latorre et al, 2018, Marín-Llauradó et al, 2022, details on this system in the next chapter. These experiments showed that elasticity measurements of the monolayer were two orders of magnitude larger than those of individual cellular parts, and the monolayer could sustain more than 200% strain before the rupture of cell-cell junctions.…”
Section: Mechanical Controlmentioning
confidence: 99%